Prevalence of tet(X4) in Escherichia coli From Duck Farms in Southeast China - Yu, Yang; Cui, Chao-Yue; Kuang, Xu; Chen, Chong; Wang, Min-Ge; Liao, Xiao-Ping; Sun, Jian; Liu, Ya-Hong (Frontiers in Microbiology, 2021)
Objectives: Carbapenems, colistin and tigecycline are critically important antibiotics in clinics and tigecycline is considered the last-resort drug against severe human infections caused by multi-drug resistant bacteria. This is especially true after the global appearance of blaNDM and mcr mediating the resistance to carbapenems and colistin respectively. Recently, a mobile tigecycline resistance gene tet(X4) has been identified in Escherichia coli, Klebsiella pneumoniae and Acinetobacter baumannii that causes high resistance to tigecycline and other tetracyclines. In this study, the prevalence of tet(X4) in E. coli isolates from duck farms in Southeast China was identified and characterized. Methods: Feces, soil, sewage and dust samples were collected from duck and goose farms along with the southeast coast provinces of China. Antimicrobial susceptibility testing and PCR screen were performed to investigate the phenotype and genotype of tigecycline resistance. Conjugation, S1-PFGE, and WGS were used to determine the transferability, location of tet(X4) gene, and further study the bacterial genomic profiles. Results: We collected 1716 samples and 16 isolates (0.9%) were identified carrying the tet(X4) gene with tigecycline MICs ≥ 8 mg/L. Notably, among all tet(X4)-positive strains isolated from Yancheng, Jiangsu, 45% of them was from the environment (soil and sewage). Sequencing analysis demonstrated these isolates belonged to diverse sequence types, mostly ST3997 from Jiangsu province. Conjugation assay to E. coli C600 was succeeded for 11 isolates, and correspondingly IncHI1- and IncX1-plasmids bearing tet(X4) were detected by sequence analysis. tet(X4) was found adjacent to an insertion sequence ISCR2 downstream and a catD gene upstream for all isolates. In addition, multiple-drug resistance to meropenem, ceftazidime, ampicillin, ciprofloxacin, trimethoprim/sulfamethoxazole and fosfomycin was profiled in all the tet(X4)-positive isolates. Conclusions: The identification of tet(X4) harboring E. coli strains in duck farms and their surroundings enlarges our knowledge of the variety and prevalence of tigecycline resistance and highlights the necessity of optimising the duck-fish production system for preventing dissemination of antimicrobial resistance genes. Additionally, the prevalence of tet(X4) raises concern for the use of tetracyclines in animal farming and the tet(X4) gene should be listed as primary gene for resistance surveillance.